The use of the CD-ROM Medline in the Medical Library University Of Malaya - Chan, S.N.; Haliza, Y. (University of Malaya Library, 1992)
CD-ROM technology was introduced to the Medical Library of the University of Malaya with the purchase of the Medline, Popline and PDQ/Cancerlit on CD-ROM in early 1990. The experiences of the Medical Library in the setting up of the CD-ROM service and the feedback obtained from users' questionnaire are presented in this paper. Suggestions from users to improve the service includes the additin of more work stations and the extension of access beyond office hours for existing work station.